Reading for gain or reading for fun: empirical evidence from China on the adoption mechanism of integrated children’s books - Cui, Jiayong; Guo, Jing; Yang, Jiaomin; Wu, Lingyu; Bao, Yinuo (Frontiers in Psychology, 2024)
Introduction With the increasing number of children’s publications that integrate new media technologies in the global publishing community, understanding the adoption and use of these publications from a child’s perspective is of great significance for both children’s education practitioners and the publishing industry. Methods This article integrates a dual-effect path based on the utilitarian-motivation system (UMS) and hedonic-motivation system (HMS) on information technology adoption via a questionnaire, systematically demonstrating the psychological mechanism of children’s reading with respect to integrated books. Results This study finds that children’s willingness to use integrated children’s books is related to UMS and HMS except for facilitating conditions. In addition, this study also reveals the structural differences existing in the adoption psychology of children from various age groups and home education backgrounds. Discussion This study provides a systematic explanation for understanding the adoption psychology of integrated children’s books. Based on these findings, it is suggested that publishers should balance the concepts of education orientation and child orientation when producing children’s books, conduct technical innovation of children’s books according to individual children, and constantly innovate the service mode to avoid the risk of children’s bad reading.